TRiDS: Treatments for Risks in Design Science - Venable, John; vom Brocke, Jan; Winter, Robert (2017)
Conducting Design Science Research (DSR) has many risks. Extant literature, such as the Risk Management Framework for Design Science Research (RMF4DSR), provides advice for identifying risks, but provides few suggestions for specific treatments for the kinds of risks that potentially plague DSR. This paper analyses known DSR risks from RMF4DSR, augments them with other risks identified, and develops a purposeful artefact (TRiDS: Treatments for Risks in Design Science), which provides 46 specific suggestions for treating known risks in DSR. The treatments identified are classified into 13 different categories and reference is made to relevant literature for guiding the application of each treatment. The treatment suggestions and guidance serve as a supplement to existing frameworks and methods for risk identification and management in DSR.